Climate Resilient and Sustainable Infrastructures: Geotechnical Challenges of Problematic Soils in Nigeria - Eze, Kelechi Nnaji; Anosike, Chukwuemeka Uchenna; Eze, Favour Nnennaya; Enabulele, Ewemade Cornelius; Benson, Kenneth Philips (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Climate change adaptation and sustainable infrastructure development are important in Nigeria due to different climate zones and poor soil types like expansive clays, laterite and peat grounds. The review highlights the necessity of incorporating climate change adaptation into infrastructure development processes to minimise the potential impacts of direct climate change phenomena, including extreme rainfall, flood, and temperature. It emphasises the importance of geotechnical engineering in tackling such challenges and advancing tools and frameworks required for constructing structures that successfully counter the undesirable soil responses caused by climate change.
Keywords: geotechnical engineering; sustainable infrastructure; problematic soils; climate resilience